Tes dan Pengukuran Kondisi Fisik Pada Atlet PORPROV 2022 - Ervan Kastrena; Aziz Amrulloh; Asep Ramdan Afriyuandi; Taupik Rochman; Muhamad Guntur Gaos Sungkawa; Goesti Sabda Laksana; Mela Aryani; Muhamad Syamsul Taufik; Edi Setiawan (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The purpose of this research is community service to carry out tests and measurements of the physical condition of Porprov athletes in 2022. The research method used is in the form of community service through test surveys and physical condition measurements. There are several stages of the activity carried out, namely the explanation of the chairman of the implementation of the activity to the athletes, an explanation of the procedure for carrying out the sit and reach test, vertical jump, sprint run, push up, sit up, squat jump, back up, side step test and beep test, collection test result data, evaluation. The results of the community service research conducted by the Tri Dharma College between the Physical Education, Health and Recreation Study Programs from Suryakancana University and the Cianjur Indonesian National Sports Committee on 378 athletes from 38 sports branches found that the physical conditions possessed by the athletes varied from low to low, moderate to good. It is hoped that this activity will continue to be carried out and synergized from year to year, so that it can become a training for athletes to achieve achievements in the future